2010
DOI: 10.1159/000320312
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Reactive Oxygen Metabolites and Carotid Intima-Media Thickness in Subjects with Hypercholesterolemia

Abstract: Objective: It was the aim of this study to investigate whether there is any relationship between oxidative stress, as assessed by the diacron reactive oxygen metabolite (d-ROM) test, and carotid atherosclerosis among hypercholesterolemic patients. Subjects and Methods: A well-defined group of patients with type II hypercholesterolemia (n = 81, mean age 59 years) was studied to observe the correlation between the levels of serum d-ROMs and carotid artery intima-media thickness (IMT) using B-mode ultrasound, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
(13 reference statements)
1
21
2
Order By: Relevance
“…CIMT is measured noninvasively by ultrasonography and is a well-established index of early-stage atherosclerosis [25,26]. Our finding that CIMT is increased in patients with CSX in spite of angiographically normal coronary arteries confirms these previous findings [27,28].…”
Section: Discussionsupporting
confidence: 89%
“…CIMT is measured noninvasively by ultrasonography and is a well-established index of early-stage atherosclerosis [25,26]. Our finding that CIMT is increased in patients with CSX in spite of angiographically normal coronary arteries confirms these previous findings [27,28].…”
Section: Discussionsupporting
confidence: 89%
“…28) However, our findings showed that dROMs were not correlated with carotid artery IMT in our cohort. Forty-four percent of the subjects in our cohort were either healthy participants or subjects with mild disease conditions, which is likely reflected in the relatively narrow range of carotid artery IMT values between 0.44 and 1.12 mm in our cohort and may be responsible for the lack of significant associations between d-ROMs and carotid artery IMT.…”
Section: Discussioncontrasting
confidence: 74%
“…26,27) Because oxidative stress has been shown to represent the balance of production of ROS and antioxidant capacity, it is more appropriate to evaluate ROS and antioxidant capacity simultaneously. However, only one study has reported an association between d-ROMs and carotid artery IMT in patients with hypercholesterolemia, 28) and, thus far, no study has examined the associations among d-ROMs, BAP values, and carotid artery IMT concurrently. Therefore, we measured d-ROMs and BAP values as indices for ROS production and antioxidant potential, respectively, and carotid artery IMT within the same subjects to investigate the association between carotid artery IMT and clinical parameters values, including d-ROMs and BAP.…”
mentioning
confidence: 99%
“…For instance, clinical studies have demonstrated that high ROM levels could be a predictor of cardiovascular disease progression [36, 37]. It is also known that high ROM levels are an independent predictor of obesity (odds ratio: 2.5; P < 0.001) in women [38].…”
Section: Discussionmentioning
confidence: 99%